Effect of size and charge on endocytosis of lysozyme derivatives by sinusoidal rat liver cells in vivo - Kooistra, Teake; Duursma, Anneke M.; Bouma, Joop M.W.; Gruber, Max (Biochimica et biophysica acta, 1980)
Hen egg-white lysozyme has been modified by intermolecular cross-linking with dimethyl suberimidate or by acylation with acetic or succinic anhydride. Retention of the native conformation of the modified enzyme was checked by measuring enzyme activity, resistance of disulfide bridges to reduction by thiols, and susceptibility to proteases. Unmodified lysozyme and its derivatives (labelled with 125I) were intravenously injected into nephrectomized rats, and plasma clearance and uptake by liver cells were determined. Under these conditions, about 6% of the unmodified lysozyme was taken up by liver 15 min after injection. Cross-linking led to a greatly increased uptake (up to 89% of the dose in 15 min), whereas acylation reduced the uptake to 3–4%. Cell isolations showed that the unmodified enzyme and the cross-linked derivatives were taken up by sinusoidal cells. Differential fractionation of liver homogenates indicated that the unmodified enzyme was taken up in lysosomes. The cross-linked derivatives were concentrated in the nuclear and microsomal fractions as well as in the lysosomal fraction, suggesting adsorption on plasma membranes besides uptake in lysosomes. The experiments described in this paper, together with previous results on ribonuclease and lactate dehydrogenase, indicate that endocytosis of some proteins by sinusoidal liver cells is positively correlated with size and positive charge of the molecules.